Analisis Pengaruh Variabel-Variabel Makro Ekonomi Terhadap Jakarta Islamic Indeks (JII) Periode 2007-2015 - Nining Khoirun Nisa; Raditya Sukmana (Universitas Airlangga, 2017)
Based on this, researchers are interested to know and analyze the effect of macroeconomic indicators consisting of Inflation, Interest Rate, Foreign Exchange and Production Index on Stock Price Index of the Jakarta Islamic Index (JII). This study uses a quantitative approach. The sampling technique used is the technique of sampling nonprobabilitas. The type of data in this study of time series data.The results of this study indicate that inflation and interest rates significantly affect the stock price index Jakarta Islamic Index (JII). Foreign exchange rates and the production index did not significantly affect the stock price index Jakarta Islamic Index (JII).